Enhancing quality through postgraduate supervision remodeling in higher education institutions - Melefetsane Mofolo; Yusuf Lukman (Insights into Regional Development)
The demand for a postgraduate qualification in South Africa has increased due to the Department of Higher Education and training requirement for a Master’s degree as the minimum qualification for teaching in universities. However, low completion rates and inferior quality dissertations and theses suggest that these ideals may not be achievable. This study juxtaposed research supervision models and suggested a framework envisaged to promote quality in the exercise. The world’s countries, including South Africa, are paying far more attention than ever to supervising postgraduate students. This can be attributed to a variety of factors. For example, diversity and massification issues have put doctoral students' supervision at the centre. In response to these demands, some scholars have emphasised the relevance and suitability of supervision models. As part of the qualitative method, document analysis was used to analyse the supervision models most higher education institutions prescribed in their Policies around the Eastern Cape in South Africa. Among the findings, the policies and their Guide focus on two types of supervision: one-on-one and co-supervision. Regrettably, neither the Policies nor the Guide mention group supervision practices. The finding further revealed that no one ultimate model may guarantee optimal productivity. Hence, more is needed to assist supervisors in delivering excellent supervision. The partnership's efficacy and robustness in supervision rely on trust, commitment, and sound communication. Hence, the researchers developed and recommended the Triple C and Double T framework, a comprehensive and dynamic model, for higher education institutions to be considered for supervision. It is further recommended that the variables in the concept be used to develop the hypothesis and research objectives.